SOSIALISASI PENGGUNAAN APLIKASI PENGARSIPAN SURAT DI SEKOLAH MENENGAH ATS NEGERI 4 PALANGKA RAYA BERBASIS WEB: Socialization of the Use of Web-Based Letter Archiving Application at State Senior High School 4 Palangka Raya" - Hotmian Sitohang; Akmal Winandi; Apriyana; Rizal Firmansyah; Yuliarti (JPMTT (Jurnal Pengabdian Masyarakat Teknologi Terbarukan), 2023)
Currently, technological advancements are progressing rapidly. Nowadays, almost everything can be done digitally using technology. Web-based applications are widely used in various fields, such as financial management applications, employee data management applications, and various others. One of these applications is document archiving, which is essential for managing information in various institutions, including Palangkaraya Public High School 4 (SMAN 4). The term "archive" originates from the Greek language, "Archivum" or "Archeon," which means a place for storing government-related documents. Letter archiving is a crucial component of information management, and SMAN 4 Palangkaraya has not had a letter archiving application in place. They have been relying on manual archiving methods, which come with several issues, including the need for significant physical space, susceptibility to damage, difficulties in retrieval, maintenance costs, and the risk of data loss. To address these issues, a community service team has developed a web-based letter archiving application using PHP and the CodeIgniter 3 framework. This application enables users to archive and manage letters digitally. After building the application, the community service team also conducted a campaign to promote the use of the letter archiving application, held at the administrative office of SMAN 4 Palangkaraya. With a large number of students and teachers, SMAN 4 Palangkaraya can utilize this technology to enhance efficiency and transparency in their letter archiving processes.